Gut microbiota composition alteration analysis and functional categorization in children with growth hormone deficiency - Huang, Congfu; Meng, Dongming; Li, Yinhu; Lu, Shiyang; Yang, Wei; Wu, Bin; Chen, Shufen; Yang, Zhenyu; Liu, Haiying (Frontiers in Pediatrics, 2023)
Objective To study changes in the composition and functions of the gut microbiota (GM) in children with growth hormone deficiency (GHD) using high-throughput sequencing. Methods Thirty-three children with GHD diagnosed in Longgang District Maternity and Child Health Hospital were included in the disease group and 24 healthy children of the same age comprised the control group. Total DNA was extracted and amplified from stool samples obtained from all subjects. High-throughput sequencing was used to analyze the GM composition and functions. Results The GM from the two groups of children showed significant differences in α-diversity (P < 0.05). In comparison with the control group, the abundance of the phylum Bacteroidetes was significantly higher (45.96% vs. 65.71%) while the Firmicutes count was significantly lower (47.09% vs. 25.20%). At the genus level, the abundance of Prevotella in the disease group was significantly higher (3.16% vs. 20.67%) and that of Lachnospiracea incertae sedis, Clostridium XlVa, and Megamonas was lower (6.576% vs. 1.75%; 4.51% vs. 0.80%; 5.08% vs. 2.02%, respectively). GM functions, including those involved in membrane_transport, energy_metabolism, poorly_characterized, metabolism_of_cofactors_and_vitamins, glycan_biosynthesis_and_metabolism, transcription, folding,_sorting,_and_degradation, were significantly altered in the disease group. The abundance of various GM components was correlated with endocrine hormone levels. Conclusion Significant alterations in the GM are seen in children with growth hormone deficiency, which may affect both energy metabolism and the levels of endocrine hormones, potentially leading to growth restriction.